Modal auxiliary verbs used in Malaysian English language secondary school textbooks - Khojasteh, Laleh (2012)
Due to the reported difficulties of Malaysian learners in terms of syntactic and semantic functions of modal auxiliary verbs in English, this research investigated 1) the ways in which nine modal auxiliaries are introduced and presented in texts and exercises, 2) modal verb phrase structures, 3) modal auxiliaries’ semantic functions, and 4) the frequency occurrence of these modal auxiliaries in both written and spoken text types as well as spoken text type in five Malaysian English language textbooks used in the secondary school level. This was addressed in four research questions and the design applied was qualitative content corpus analysis. The findings of this study have shown several valuable insights. Firstly, from the discussion of the grammatical progression in the textbooks, we can see that the presentation of modal auxiliary verbs in Malaysian English language textbooks is not fully in accordance with their use in natural English, and that textbook writers tended to emphasize only certain semantic functions at the expense of others. Furthermore, frequency information on pragmatic functions has not been taken into account by Malaysian textbook authors. Similarly, there are very great differences in the relative frequency of use of nine verb phrase structures in which modals can occur. In terms of modal auxiliaries and their semantic functions, the findings show that these textbooks offer a relatively biased-picture, overemphasizing the minor semantic functions and overlooking the frequent functions used in present-day English. It is also argued that although there are invaluable insights available in terms of modal auxiliary verb forms and their semantic functions in major corpus-based studies, this real-life language has not been well presented in Malaysian English language textbooks. Finally, the frequency and ranked order of modal auxiliary verbs in the English language textbooks used in Form 1, 2, 3, 4 and 5 in Malaysian secondary schools are presented in a descending order: can, will, should, would, may, must, could, might and shall. This finding shows that for almost all of the modal auxiliaries, there is a discrepancy between frequency order in the textbook corpus and the three major reference corpora. For example, although would and could are among the most frequent modals in real language, it is both a surprise and a concern to see that the both modals are neither among the top four most frequent modals in the textbook corpus nor are they even introduced to secondary learners. The findings of this study also show that the most frequent modals featuring spoken language are not dealt with sufficiently in the currently used pedagogical language in the Malaysian textbooks. Findings from this corpus-based study tend to provide a sense of familiarity with five prescribed textbooks’ content, thus assisting educators in identifying the particular strengths and weaknesses in textbooks already in use and helping them to overcome the discrepancies in order to achieve a higher degree of authenticity in textbook corpus. This level of awareness of modal auxiliary verbs and familiarity with them would also go a long way in ultimately assisting teachers with making optimum use of a textbook’s strong points, recognizing the shortcomings of certain exercises, tasks, and entire texts.